Framework COBIT 2019: Analisis dan Desain Tata Kelola Teknologi Informasi (Studi Kasus pada CV Ifadah Daya Bersama) - Rasmila, Rasmila; Riansyah, Septa; Firnando, M. Iksan; Wahyudi, Muhammad Rizki; Anugrah, M. Fani (Training and Research Institute Jeramba Ilmu Sukses (TRI - JIS), 2025)
Information technology (IT) governance is an alignment practice that is tailored to the company's goals, so that it can help the company compete with other competitors. The implementation of IT based on the COBIT 2019 framework is intended to help improve the success of the company's performance. In the current industrial era, many advances have occurred, such as the emergence of online stores that have a high level of competitiveness, including the corporate sector. So that the problems identified in the company CV Ifadadah Daya Bersama are still carrying out company activities traditionally by not implementing a comprehensive IT governance evaluation, so there are problems in managing internal ordering information and inventory data. The analysis is carried out based on the system of online company activities by adopting COBIT 2019.